Rodents as Sentinels for the Prevalence of Tick-Borne Encephalitis Virus - Achazi, K.; Růžek, D. (Daniel); Donoso-Mantke, O.; Schlegel, M.; Ali, H. S.; Wenk, M.; Schmidt-Chanasit, J.; Ohlmeyer, L.; Ruhe, F.; Vor, T.; Kiffner, Ch.; Kallies, R.; et al. (Vector-Borne and Zoonotic Diseases, 2011)
Tick-borne encephalitis virus (TBEV) causes one of the most important flavivirus infections of the central nervous system, affecting humans in Europe and Asia. To test the suitability of rodents as a surrogate marker for virus spread, laboratory-bred Microtus arvalis voles were experimentally infected with TBEV and analyzed over a period of 100 days by real-time (RT)-quantitative PCR. Further, the prevalence of TBEV in rodents trapped in Brandenburg (Germany) was determined. In experimentally infected M. arvalis voles, TBEV was detectable in different organs for at least 3 months and in blood for 1 month. 10% of all rodents investigated were positive for TBEV. TBEV was detected in 6 rodent species: Apodemus agrarius, Apodemus flavicollis, Apodemus sylvaticus, Microtus agrestis, Microtus arvalis, and Myodes glareolus. M. glareolus showed a high infection rate in all areas investigated. These voles developed a persistent TBE infection without clinical symptoms.